Unprecedented visible light-initiated topochemical [2 + 2] cycloaddition in a functionalized bimane dye - Dvoracek, Metodej; Twamley, Brendan; Senge, Mathias O.; Filatov, Mikhail A. (Beilstein Journal of Organic Chemistry, 2025)
Bimanes, a class of molecules based on the 1H,7H-pyrazolo[1,2-a]pyrazole-1,7-dione scaffold, were first introduced by E. M. Kosower in 1978. In this study, we report the topochemical cycloaddition of diethyl 2,6-dichloro-1,7-dioxo-1H,7H-pyrazolo[1,2-a]pyrazole-3,5-dicarboxylate (Cl2B), initiated by visible light. Crystal structure analysis confirmed that the reactive double bonds are parallel and coplanar, in line with the Schmidt criteria for topochemical cycloaddition. Additionally, two other bimane derivatives with different substitution patterns were synthesized and investigated. Our findings suggest that functionalizing bimanes to redshift their absorption maxima into the visible-light spectrum provides a promising strategy for synthesizing substituted cyclobutanes without the need for ultraviolet irradiation.
Keywords: bimane; [2 + 2] cycloaddition; fluorescence; topochemical polymerization; X-ray crystallography